2020
DOI: 10.1002/ejoc.202001097
|View full text |Cite
|
Sign up to set email alerts
|

One‐Pot Transfer Hydrogenation Reductive Amination of Aldehydes and Ketones by Iridium Complexes “on Water”

Abstract: An efficient and practical one‐pot transfer hydrogenation reductive amination of aldehydes and ketones with amines has been developed by using iridium complexes as catalysts and formic acid as hydrogen source in aqueous solution, providing an environmentally friendly methodology for the construction of a wide range of functionalized amine compounds in excellent yields (≈ 80 %‐95 %). This effective methodology can be scaled up to gram scale with 0.1 mol‐% catalyst loading and also be employed in the synthesis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 100 publications
1
12
0
Order By: Relevance
“…Recently, we developed a similar direct reductive amination procedure with the iridium complex C6 as the catalyst (Scheme 22). 62 This method was shown to be tolerant to various aldehydes/ketones and amines, leading to amine products in excellent yields under mild conditions. Using this strategy, the anti-motion sickness drug of meclizine was installed in onestep, which evidenced the practicability of this methodology.…”
Section: Direct Reductive Amination (Dar)mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we developed a similar direct reductive amination procedure with the iridium complex C6 as the catalyst (Scheme 22). 62 This method was shown to be tolerant to various aldehydes/ketones and amines, leading to amine products in excellent yields under mild conditions. Using this strategy, the anti-motion sickness drug of meclizine was installed in onestep, which evidenced the practicability of this methodology.…”
Section: Direct Reductive Amination (Dar)mentioning
confidence: 99%
“…60 Scheme 22 Direct reductive amination of ketones by Cp*Ir-pyridineimidazoline. 62 Scheme 19 Asymmetric transfer hydrogenation of N-aryl imines. 57 Scheme 23 Direct reductive amination of ketones/aldehydes with HCOONH 4 .…”
Section: Direct Reductive Amination (Dar)mentioning
confidence: 99%
“…With our continued interest in iridium complex-catalyzed transfer hydrogenation, we found that Ir–H complexes could be obtained by the decomposition of formic acid through iridium complexes. 22 By designing and synthesizing a series of achiral and chiral iridium complexes, we envision that the reductive Ir–H complexes could contribute to the synthesis of tetrahydroquinolines.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our group was devoted to the application of catalytic reactions with iridium complexes catalysts and developed some efficient catalytic methodologies using water as the solvent [22] . For example, we had developed the iridium complex‐catalyzed N ‐alkylation of amines with alcohols [22c] and reductive amination of aldehydes and ketones [22d] in water. According to our previous work, we have the following findings: (1) The mechanism of N ‐alkylation of amines with alcohols went through the dehydrogenative process of alcohol, which indicated the iridium catalysts could promote dehydrogenation of alcohols; [22c] (2) Study on chemoselective transfer hydrogenation of transformation demonstrated the iridium catalysts could realize a selective reduction of α , β ‐unsaturated compounds; [22a] For example, When HCOOH is used as the hydrogen donor (pH≈3), intermediate A is formed through a four‐membered transition state.…”
Section: Introductionmentioning
confidence: 99%